PENGARUH KOMPETENSI APARATUR PEMERINTAH, PENGENDALIAN AKUNTANSI, KETAATAN PADA PERATURAN PERUNDANG-UNDANGAN, DAN PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (STUDI EMPIRIS PADA OPD DI PEKANBARU) - Rosalia Hery; M. Rasuli M. Rasuli; Kurnia Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study was aimed to examine the influence of government apparatus competency, accounting control, adherence to rule of law, and budgetary participation on performance accountability of government entity. sample of this study is regional apparatus organization of pekanbaru city. The sampling method is used purposive sampling methode with total 99 respondents and the population 45 regional apparatus organization used in this study. The data source used in the study was the primary data. Analysis of data is carried out using multiple regression analysis with the program of SPSS version 23.0 windows. The result proved that: (1) government apparatus competency had a effect on performance accountability of government entity. (2) accounting control had a effect on performance accountability of government entity. (3) adherence to rule of law had effect on performance accountability of government entity. (4) budgetary participation had a effect on performance accountability of government entity.Keyword: Government Apparatus Competency, Accounting Control, Adherence To Rule Of Law, Budgetary Participation, Performance Accountability Of Government Entity